Forvaltningen af det bestående:: Guvernementalitet, regering og økonomi hos Giorgio Agamben - Jessen, Mathias Hein (Slagmark - Tidsskrift for idéhistorie, 2015)
The article investigates Giorgio Agamben’s turn to, and radicalization of, Foucault’s concept of governmentality, which Agamben argues constitutes a ’decisive point’ in the Homo sacer-series. The article shows that in the investigation of the Trinitarian oikonomia, Agamben finds the point of intersection between the ‘totalizing procedures’ of the state and ‘individualizing techniques’ of biopolitics thereby disclosing the ‘zone of indistinction’ between sovereignty and government and politics and economy, which constitutes power in the West. Furthermore, the article argues that Agamben shows how the economy is not something distinct from politics, encroaching on its logic, but rather how the governmental paradigm of the West constitutes the continual administration of the given, the continual and perpetual government of the economy and thereby of the existing economic and political power-relations.